Method and apparatus for spectral strain rate visualization - HEIMDAL ANDREAS; TORP HANS GARMANN (2003)
Methods and apparatus are provided in a diagnostic ultrasound system for generating and displaying strain rate spectrums corresponding to the deformation of a tissue structure within a subject, designated by a sample gate, in response to Doppler signals generated by the ultrasound system. Various combinations of several processing techniques are employed including spectral estimation processing such as discrete Fourier transform (DFT) processing, circular convolution, signal scaling/normalization, and complex autocorrelation.